Efficacy of left subclavian artery revascularization strategies during thoracic endovascular aortic repair in patients with type B dissection: A single-center experience of 105 patients - Wu, Xiangyang; Li, Yongnan; Zhao, Yinglu; Zhu, Yilin; Wang, Shixiong; Ma, Qi; Liu, Debin; Gao, Bingren; Wei, Shilin; Wang, Weifan (Frontiers in Cardiovascular Medicine, 2023)
Background Left subclavian artery (LSA) revascularization during thoracic endovascular aortic repair (TEVAR) is necessary to reduce postoperative complications in patients with Stanford type B aortic dissection and an insufficient proximal anchoring area. However, the efficacy and safety of different LSA revascularization strategies remain unclear. Here, we compared these strategies to provide a clinical basis for selecting an appropriate LSA revascularization method. Methods In this study, we included 105 patients with type B aortic dissection who were treated using TEVAR combined with LSA reconstruction in the Second Hospital of Lanzhou University from March 2013 to 2020. They were divided into four groups according to the method used for LSA reconstruction, namely, carotid subclavian bypass (CSB; n = 41), chimney graft (CG; n = 29), single-branched stent graft (SBSG; n = 21), and physician-made fenestration (PMF; n = 14) groups. Finally, we collected and analyzed the baseline, perioperative, operative, postoperative, and follow-up data of the patients. Results The treatment success rate was 100% in all the groups, and CSB + TEVAR was the most commonly used procedure in emergency settings compared with the other three procedures (P < 0.05). The estimated blood loss, contrast agent volume, fluoroscopic time, operation time, and limb ischemia symptoms during the follow-up were significantly different in the four groups (P < 0.05). Pairwise comparison among groups indicated that the estimated blood loss and operation time in the CSB group were the highest (adjusted P < 0.0083; P < 0.05). The contrast agent volume and fluoroscopy duration were the highest in the SBSG groups, followed by PMF, CG, and CSB groups. The incidence of limb ischemia symptoms was the highest in the PMF group (28.6%) during the follow-up. The incidence of complications (except limb ischemia symptoms) during the perioperative and follow-up periods was similar among the four groups (P > 0.05) The median follow-up time of CSB, CG, SBSG, and PMF groups was significantly different (P < 0.05), and the CSB group had the longest follow-up. Conclusion Our single-center experience suggested that the PMF technique increased the risk of limb ischemia symptoms. The other three strategies effectively and safely restored LSA perfusion in patients with type B aortic dissection and had comparable complications. Overall, different LSA revascularization techniques have their advantages and disadvantages.